Hubungan Perilaku Pemberantasan Sarang Nyamuk (PSN) Dengan Keberadaan Larva Aedes aegypti Di Desa Bonto Mate’ne Kecamatan Mandai Kabupaten Maros - Sulasmi, Sulasmi; Haderiah, Haderiah; Firliana, Firliana (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
The behavior of the community that still pays less attention to PSN so that Larvae can be at risk of causing DBD. Based on data from the Maros Regency Health Office, Mandai District is the area with the highest number of DBD cases in Maros Regency. The purpose of this study was to determine the Behavior of PSN with the Presence of Aedes aegypti Larvae in Bonto Mate'ne Village, Mandai District, Maros Regency. This study was an analytical observational study with a Cross Sectional design using the Chi Square Test. The study was conducted at a residence in Bonto Mate'ne Village, Mandai District, Maros Regency which had a sample size of 78 houses. The results of this study indicate that there is a significant relationship between community knowledge, attitudes, and actions related to PSN and the presence of Aedes aegypti larvae in Bonto Mate'ne Village, Mandai District, Maros Regency (p = 0.042 < α = 0.05), where the p-value is smaller than the alpha value. The conclusion of this study is that there is a relationship between Knowledge, Attitudes, and Actions related to PSN with the Presence of Aedes aegypti Larvae in Bonto Mate'ne Village, Mandai District, Maros Regency. It is hoped that the relevant agencies and the community can work together in handling Aedes aegypti mosquito nests by conducting counseling and actions, especially in efforts to Eradicating Mosquito Nests with 3M Plus which is carried out once a week. Keywords : Mosquito Nest Eradication (PSN); Aedes aegypti larvae